2022
DOI: 10.3390/molecules27144610
|View full text |Cite
|
Sign up to set email alerts
|

Thiosemicarbazide-Substituted Coumarins as Selective Inhibitors of the Tumor Associated Human Carbonic Anhydrases IX and XII

Abstract: A novel series of thiosemicarbazide-substituted coumarins was synthesized and the inhibitory effects against four physiologically relevant carbonic anhydrase isoforms I, II, IX and XII showed selective activities on the tumor-associated IX and XII isozymes. Molecular modeling studies on selected compounds 14a and 22a were performed. The binding modes of such compounds were determined assuming their enzymatically active structures (i.e., cinnamic acid) in the thermodynamically favored, and not previously explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Second, compounds 103(a-o) were reacted with propargyl bromide to produce compounds N-alkyl-3-prop-2-yn-1-ylthio)-5H- [1,2,4]triazino [5,6b] indole derivatives 104(a-o) followed by the reaction with Newly synthesized compounds 105(a-o) were screened for inhibitory activity against human (h) isoforms of CA, hCA I, II, XIII (cytosolic isoforms), and hCA IX (tumor related isoform) by the stopped-flow CO 2 hydrase assay method by taking AAZ as standard drug and it was observed that 105i (X = F, R = -CH (CH 3 ) 2 ) was found to show potent activity against hCA II and hCA XIII with K i values of 7.7 and 34.9 nM, respectively, as compared to AAZ (K i = 12.1 nM) due to the presence of fluoro-group at fifth position of indole moiety and isopropyl group attached to nitrogen of indole ring [34] (Scheme 15). (110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126)(127)(128)(129).…”
Section: S C H E M E Synthesis Of 94(a-s)mentioning
confidence: 99%
See 2 more Smart Citations
“…Second, compounds 103(a-o) were reacted with propargyl bromide to produce compounds N-alkyl-3-prop-2-yn-1-ylthio)-5H- [1,2,4]triazino [5,6b] indole derivatives 104(a-o) followed by the reaction with Newly synthesized compounds 105(a-o) were screened for inhibitory activity against human (h) isoforms of CA, hCA I, II, XIII (cytosolic isoforms), and hCA IX (tumor related isoform) by the stopped-flow CO 2 hydrase assay method by taking AAZ as standard drug and it was observed that 105i (X = F, R = -CH (CH 3 ) 2 ) was found to show potent activity against hCA II and hCA XIII with K i values of 7.7 and 34.9 nM, respectively, as compared to AAZ (K i = 12.1 nM) due to the presence of fluoro-group at fifth position of indole moiety and isopropyl group attached to nitrogen of indole ring [34] (Scheme 15). (110)(111)(112)(113)(114)(115)(116)(117)(118)(119)(120)(121)(122)(123)(124)(125)(126)(127)(128)(129).…”
Section: S C H E M E Synthesis Of 94(a-s)mentioning
confidence: 99%
“…were docked into active sites of hCA IX and XII. It was observed that these compounds showed good binding affinity and proved to be potent inhibitors [113] (Scheme 96). Newly synthesized compounds were evaluated for in vitro inhibitory activity against hCA I, II, IV, VII, IX, and XII using stopped flow CO 2 hydrase assay by taking AAZ as standard drug and it was observed that 733d (n = 1) was found to show potent activity against hCA I, II, IV, VII, IX, and XII with K i values of 78.2, 2.8, 1013, 8.9, 13.2, and 6.5 nM, respectively, as compared to AAZ (250, 12, 74, 2.5, 25, and 5.7 nM), respectively.…”
Section: S C H E M E 94mentioning
confidence: 99%
See 1 more Smart Citation